2022
DOI: 10.3390/ph15121585
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Permeation Enhancers for the Development of Oral Peptide Pharmaceuticals

Abstract: Recently, two oral-administered peptide pharmaceuticals, semaglutide and octreotide, have been developed and are considered as a breakthrough in peptide and protein drug delivery system development. In 2019, the Food and Drug Administration (FDA) approved an oral dosage form of semaglutide developed by Novo Nordisk (Rybelsus®) for the treatment of type 2 diabetes. Subsequently, the octreotide capsule (Mycapssa®), developed through Chiasma’s Transient Permeation Enhancer (TPE) technology, also received FDA appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 150 publications
0
3
0
Order By: Relevance
“…It should also be noted that the 5 days preterm and 5 days near-term received different infant formulas, which may have contributed to the characteristics of mucus. Furthermore, although C10 is approved as a food additive 56 , used in infant formula 17 , and tested at the gram scale without any reported genotoxicity or subchronic toxicity 57 , this compound is also known to increase transmucosal permeation of macromolecules when used within a two- to three-digit mM range in rodents in vivo 58 , 59 . Nevertheless, further work is needed to understand how C10 interacts with mucus and explore any opportunities to improve conditions with impaired mucus barrier.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that the 5 days preterm and 5 days near-term received different infant formulas, which may have contributed to the characteristics of mucus. Furthermore, although C10 is approved as a food additive 56 , used in infant formula 17 , and tested at the gram scale without any reported genotoxicity or subchronic toxicity 57 , this compound is also known to increase transmucosal permeation of macromolecules when used within a two- to three-digit mM range in rodents in vivo 58 , 59 . Nevertheless, further work is needed to understand how C10 interacts with mucus and explore any opportunities to improve conditions with impaired mucus barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, EDTA 2Na is known to increase the paracellular transport of hydrophilic compounds in a concentration-dependent manner in Caco-2 cells in vitro and in rats in situ and in vivo. It was also reported that, after the application of high EDTA concentrations of more than 6 mM (2.02 mg/mL) for 45 min, the transepithelial electrical resistance (TEER) did not recover to the TEER value before EDTA treatment, but, at the lower concentrations of EDTA such as 2 and 3 mM (1.01 mg/mL), the TEER recovered again while the permeability of sodium fluorescein remained at an elevated level in Caco-2 cells [ 46 , 48 , 49 , 50 ]. In in vivo conditions, the decreased TEER recovers to the TEER value before EDTA treatment due to the re-distribution of cationic metals from blood circulation, and the elevated permeability was rapidly decreased to the level in the absence of EDTA 2Na.…”
Section: Discussionmentioning
confidence: 99%
“…To commemorate this new era of bioavailable peptide drugs, this review article summarizes the technological progress in improving the oral absorption of new drug modalities and discusses future prospects to improve absorption enhancement. Since numerous review articles about oral absorption enhancement technology have already been published [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], this manuscript provides a brief explanation of these technologies in Section 2 . However, the main focus of this manuscript involves shedding light on new aspects of orally bioavailable middle-to-large molecules, mainly based on information in the recent (from 2020 to 2023) literature available in PubMed, in order to keep readers up to date with the latest technology.…”
Section: Introductionmentioning
confidence: 99%